CLIMATIC REGIONS OF KOSOVO AND METOHIJA - Ivanović, Radomir; Valjarević, Aleksandar; Vukojičić, Danijela; Radovanović, Dragan (Bulletin of Natural Sciences Research, 2016)
The Following the average and extreme values of climatic elements, specific climatic indices and field research, we can select three climatic types in Kosovo and Metohija - the altered Mediterranean, continental and mountainous type. The altered Mediterranean type is present  in southern and western Metohija , to be specific, it affects the Prizren Field, the Suva Reka and Orahovac Valley as well as the right bank of the Beli Drim from Pecka Bistrica to the Serbia - Albania border. Gradually and practically unnoticeably, it transforms itself into a moderate continental type which dominates over the remaining valley and mountainous parts of Kosovo. It affects parts of northern Metohija, Drenica and the entire Kosovo valley along with smaller sidelong dells - Malo Kosovo and Kosovsko Pomoravlje. Because of their exquisite heights, the mountains that complete the Kosovo Metohija Valley have a specific climatic type, at their lower slopes it is sub - mountainous and at the higher ones it is typically mountainous. Within these climatic types, several climatic sub regions are present. Their frontiers are not precise or sharp. Rather, their climatic changes are gradual and moderate from one sub-region to the other.
Keywords: Kosovo and Metohija; climatic sub-regions; Climatic regions